Engaging research: Empowering ESL/EFL teachers to teach pronunciation - Kirkova-Naskova, Anastazija (Université Grenoble-Alpes, 2023)
The ongoing debate about the research-practice link has raised the point that research advances are far more progressive and teaching practice is failing to keep up. An important aspect that has received little attention is understanding teachers’ classroom reality – a reality that for many involves an ever-increasing workload, limited resources, and a lack of autonomy and self-confidence. It is evident that teachers should be encouraged to address pronunciation in their teaching more frequently. However, they also need support to navigate the personal and institutional challenges. This paper proposes a conceptual agenda which empowers teachers to learn how to reflect on their pronunciation teaching practices. Current issues in pronunciation research relevant for the teaching context are discussed, followed by an overview of the most effective research findings that can be successfully applied in the classroom. These insights are then contrasted with preliminary results from a qualitative study that investigates teachers’ experience with pronunciation teaching. In the last section, ways of providing support for teachers’ learning and professional development are explored.
Keywords: pronunciation research, pronunciation teaching, research-practice link, classroom practices, professional development